The Effect of Guide Reading and Summary Procedure (GRASP) toward the Second year Students’ Reading Comprehensions at SMA Negeri 02 Tapung Hilir - kirana, candra (Jurnal Curricula, 2018)
Guide reading and Summary Procedure (GRASP) is an innovation classroom procedure for teaching reading strategy, enable students to understand what they are reading and compose summaries of their reading. Type of this research is an experimental research with using quantitative data. It involved two class; they were experimental and control class. This research was conducted of the second year’s student at SMA Negeri 02 Tapung Hilir. The population of this research was conducted the second year’s students by using cluster sampling that consists of 52 person. The data collection technique has done by using questionnaires. The result of this research, it was found that the mean of the student’s pre-test score that consists of 55.23, while the mean of the students’ post-test score that consists of 76.15. So, there was increase point about 20.92 % from pre-test to post-test. And the other side t_obs was 3.31 and t_table was on the level of significant 1% with degree of freedom (df) = 50 was 2,66 and on the level significant 5% with degree of freedom (df) = 50 was 2,00. It means that by using Guide Reading and Summary Procedure (GRAPS) strategy gave positive improvement to the students’ reading comprehension.